Development and performance prediction of polyethersulfone-carbon molecular sieve mixed matrix membrane for CO2/CH4 separation - Nasir, R. (Italian Association of Chemical Engineering - AIDIC, 2015)
Natural gas contains some impurities liked acid gases (CO2 & H2S), which can affect the environment. Currently, the main focus of the research is to invent the new membranes materials for gas separation. Native polyethersulfone (PES) and PES/carbon molecular sieve (CMS) mixed matrix membranes were fabricated by solvent evaporation method using N-Methyl-2-pyrrolidone (NMP) as solvent. The final membranes were characterized in term of morphology and thermal stability by using field emission scanning electron microscopy (FESEM) and thermal gravimetric analyser (TGA). FESEM analysis of developed membranes was revealed that the final membranes have acceptable contacts between filler particles and the polymer chains with the thickness in the ranges from 51.37 Î¼m to 67.68 Î¼m. CMS inorganic particles were dispersed well within organic (polymer) matrix. Due to the addition of CMS the developed membrane exhibit the improved thermal stability. In the pure gas permeation, the effect of CMS loading and variable pressures (2, 4, 8 and 10 bar) on permeance and selectivity was analysed. Gas permeance and selectivity test portrayed that addition of different loading of CMS showed a better gas separation performance as compared to pure PES membranes. The results showed that the CO2 permeance and CO2/CH4 selectivity was increased with increasing CMS loading. The CO2 permeance and CO2/CH4 selectivity were increased from 50.86 GPU to 122.20 GPU and 3.08 to 10.33 at 2 bar pressure. The performance of membranes was predicted by using current numerical model of mixed matrix membranes. The current results showed that this work will be the substantial contribution in the gas separation technology. Copyright Â© 2015, AIDIC Servizi S.r.l.,.